Electric Vehicle Development And Prediction Of Battery Consumption Based On A Journey Profile - Abdul Karim, Kasrul; Othman, Md Nazri; Wan Hassan, Wan Ahmas Redhauddin; Bugis, Mohd Ismadi; Ramli, Mohd Zulkifli; Abdullah, Abdul Rahim; Jidin , Auzani (Trans Tech Publications, 2014)
The lack of internal combustion engine (ICE) for electric vehicle (EV) makes it solely dependable on battery supply. Due to this, the prediction of battery consumption becomes crucial to determine the accurate driving range before the car needs to be re-charged. The developed prediction model can also be applied as simulation tool and help in reducing the length and the cost of the EV design process. This paper presents the prediction of battery power requirement for a small re-engineered EV converted from a commercial ICE car by using vehicle dynamic mathematical equations. The prediction is performed based on multiple journey profile that gathered before the actual test. The development of re-engineered EV is also presented, along with the experimental result of an actual drive test on a racing circuit to validate the prediction model.